(3CSdhH eSJMOK ddWHGYI HGdfbd GdMQGQi ceONd dGHJcGQ CYeGd eSJdgeI ef JUhjQ bWQGJ GdejGg (B: s (3OQGSI JLQjHjI (B= An updated method for thermal transfer printing as an input to create works inspired by the photography of water droplets , Experimental study / s - (3EjeGf MSjf YHOGdMejOs; (3SejQI YHOGdaJGM GdTQja (B: s; (3Ydi eMeO GdedjLi (B: s ((3GdbGgQI (B: s (3EjeGf MSjf YHOGdMejO (B: s, 2015)
(3Jbhe GdOQGSI Ydi GSJNOGe JbfjI GdWHGYI HGdfbd GdMQGQi(B: (3HGSJNOGe CSGdjH LOjOI h eJfhYI ai GdNGeGJ h GdJbfjI faSgG(B: (3eY GdGYJeGO Ydi YfUQ GdGHJcGQ ai GdJUeje(B: (3GdfGJL ef JUhjQ bWQGJ GdejGg(B. (3CgejI GdHMK(B: (3gPG GdHMK eMGhdI dEKQGA eLGd GdJQHjI GdafjI HGdWHGYI GdjOhjI HESJNOGe GdJcfhGhLjG chSjW eJejR ai LejY eQGMd GdJUeje GdWHGYi(B: (3dEYWGA QDi LOjOI h eJYOOI ai eLGd GdJUeje GdWHGYi ceG jSGYO GdHMK ai(B: (3EfJGL h EYOGO UHZGJ NGUI JJfGSH eY COhGJ (B((3bde GdQGHjOh(B) (3JbfjI GdWHGYI HGdfbd GdMQGQi Ydi GdbeGT h JSJNOe ef NdGd JMhjd eGcjfI GdWHGYI GdfGaKI ddMHQ ddfbd GdMQGQi(B: (3h JhajQgG HCSYGQ QNjUI GdKef(B. (3GSJMOGK eONd LOjO ai GdWHGYI ef NdGd JbfjI Gdfbd GdMQGQi HJUejeGJ ef EYOGO GdWGdH Ohf hSGFW LGgR ddhQb h GYJHGQg bGdH WHGYi ef GdhQbs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdJQHjI GdfhYjI (B- (3bSe GdJQHjI GdafjIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdWHGYI GdMQGQjIs; (3GdecGHSs; (3Gdfbd GdMQGQis